The prevalence and distribution of health risk factors in airline pilots: a cross‐sectional comparison with the general population - Daniel Wilson; Matthew Driller; Ben Johnston; Nicholas Gill (Elsevier, 2022)
Abstract Objective: To explore the prevalence and distribution of health risk factors in airline pilots and compare these with the general population. Methods: Health risk measures: age, sex, weight, height, body mass index (BMI), blood pressure, sleep, physical activity (PA) and fruit and vegetable intake (FV) were analysed to determine the prevalence and distribution of health risk. Results: Obesity prevalence and BMI was lower in pilots (p=<0.001, −17.5%, d=−0.41, and p=<0.05, −1.8, d=−0.37, respectively), yet overall overweight and obesity prevalence did not differ between groups (p=0.20). No difference was observed between groups for hypertension (p=0.79, h=−0.01), yet a higher proportion of pilots were 'at risk' for hypertension (p=<0.001, h=−0.34). The general population had longer sleep duration (p=<0.001, d=0.12), achieved more total PA minutes (p=<0.001, d=0.75), and had a higher prevalence of positive self‐rated health (p=<0.001, h=0.31). More pilots achieved >5 servings of FV daily (p=0.002, h=0.16). Conclusion: Pilots had lower obesity prevalence, higher FV, yet lower positive self‐health ratings and total PA minutes, and shorter sleep duration overall. Implications for public health: The results indicate notable health risk factor prevalence in airline pilots and the general population. Based on present findings, aviation health researchers should further examine targeted, cost‐effective intervention methods for promoting healthy bodyweight, managing blood pressure, and enhancing health behaviours to mitigate the risks of occupational morbidity, medical conditions causing loss of licence, medical incapacity, and to support flight safety.